(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2016)
The premise of this issue of the journal is that in western secular democracies the principles underlying the democratic paradigm at the national level are not in any serious doubt. It is this presumption that I wish to address. This paper will assert that the citizen is no longer at the heart of the democratic process. Using the example of the UK, I will argue that this is a consequence of the representative nature of liberal democracy which conceptualises citizenship as a legal status, giving citizens protection of the law rather than participating in its formulation or execution as in the civic republican model. Liberal democracy not only eschews greater political participation, it does not prepare citizens for it. There currently exists a democratic deficit at local and national level which is leading to a decline in active citizenship. Therefore any attempt to democratise globalisation without address- ing the weakening of national democracies will simply lead to the current political elites populating new ‘democratic’ structures. With this in mind I will counter arguments utilised to discredit the civic republican model of democracy. I will argue that in England the present educational system, predicated upon a narrow skills-based agenda premised upon an economic rationale, is undermining democracy by not preparing the citizenry for active political participation or to critique governance. In addition, policy changes in England are leading to the commodification of education which will undermine its social purpose and inter alia democracy.